Developing indicators of service integration for child health: Perceptions of service providers and families of young children in a region of high need in New Zealand. (March 2015) - Pullon, Susan; McKinlay, Brodie; Yager, Jess; Duncan, Bruce; McHugh, Patrick; Dowell, Anthony
Children in many areas of New Zealand have poor health indices; statistics indicate health inequalities. Existing international indicators of child health currently take little account of local context. There are few composite indicators of how child health services are integrated at a community level. This study aimed to explore what local people consider would be useful indicators of better child health. Data for this qualitative study were collected via 24 individual interviews and two focus groups in a rural area of New Zealand. A total of 13 in-depth interviews were conducted with parents/families of small children. Participants were asked about wide-ranging aspects of child health. Also, 11 interviews and two focus groups were conducted with front line health professionals/stakeholders. Key themes from the content thematic analysis: include child health should be measured in multidimensional ways; essential interdependence of family–child health; universal access to culturally appropriate care, free primary care services and parenting education and support is needed; and there is a lack of integration and communication between health, education and social services. There is an important need to measure and monitor communication/integration across existing health, education and social services, provide better parenting support and health education and improve access to culturally appropriate primary care.